Analisis Nilai-Nilai Islam Berkemajuan Melalui Buku Ajar Kemuhammadiyahan di SMP/MTs - Maysaroh, Anisatul; Perawironegoro, Djamaluddin; Nisun, Amajida Zahara (Universitas Muhammadiyah Prof Dr Hamka, 2025)
This research aims to analyze the application of progressive Islamic values which are a theological reflection of the values of transcendence (divinity), liberation (freedom), humanization (humanity), and emancipation (equality) in Muhammadiyah education textbooks. This textbook is an important instrument designed to transfer progressive Islamic values in line with Muhammadiyah's vision and mission. The results of this research aim to analyze aspects of content, language, graphics and presentation in SMP/MTs Muhammadiyah education textbooks. This type of research is a literature study using a qualitative Library Research (library) approach using a philosophical approach. Research data was obtained through a documentation method in three stages, namely; (1) The first stage is heuristic or source collection; (2) The second stage is source criticism or verification; (3) The third stage is interpretation. The data analysis techniques used are content analysis and hermeneutics. The results of this research show that: 1) Content: SMP/MTs Muhammadiyah Education textbooks contain progressive Islamic values such as divinity, freedom, humanity and equality, both textually and contextually; 2) Language: These values are found in sentences or paragraphs that reflect attitudes according to the indicators; 3) Presentation: These values are explained through learning objectives and materials, competency tests, discussion problems, and insights; 4) Graphics: These values are also visible in logo illustrations, images and photos of association activities. From the data analysis, it can be concluded that SMP/MTs Muhammadiyah Education textbooks contain characteristics of progressive Islamic values in material, learning activities, and textual and contextual illustrations/images.